2021
DOI: 10.3390/su131910757
|View full text |Cite
|
Sign up to set email alerts
|

Digitization of the Customs Revenue Administration as a Factor of the Enhancement of the Budget Efficiency of the Russian Federation

Abstract: In this study, we analyzed the main tendencies of the digitization of the tax and customs administration in Russia and worldwide. The main focus of this study is on the determination of the role of customs payments in the enhancement of the budget efficiency of the Russian Federation. For this purpose, we carried out an analysis of the collectability of the customs payments over 18 years according to their different types. Our research showed that further development of the use of digital technologies in custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The quality of human resources has a significant effect on program implementation [45][46][47]. Similarly, financial efficiency toward goal achievement [48][49][50]. The existence of policies that restrict program implementation serves as an estuary [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of human resources has a significant effect on program implementation [45][46][47]. Similarly, financial efficiency toward goal achievement [48][49][50]. The existence of policies that restrict program implementation serves as an estuary [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of digital technology in revenue administration has only been examined by Zasko et al (2021), they indicate that which can result in better fiscal outcomes while also having wider economic ramifications for customs operations. Gruchmann et al (2020) found that digital business models and digitalization intersect to reshape business models within the sea freight industry which affects the potential for enhanced operational efficiency and effectiveness.…”
Section: Digital Taxation On Customs Efficiency and Sustainabilitymentioning
confidence: 99%
“…The findings of Fanea-Ivanovici et al ( 2019) and Ababneh et al (2023) confirmed the hypothesis that digital taxation and sustainability are positively correlated. Liu et al (2023b) and Zasko et al (2021) emphasized the advantages of digital accounting in terms of improving reporting accuracy and speeding up processing. According to Alsharari and Ikem (2023) the openness and traceability of transactions made possible by digital accounting have a favorable impact on the sustainability of customs ports.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Digitization in Customs Payment: Field of study that deals with the implementation of effective processes in customs activities, that is, fast transactions and accountability during the entry-exit of cargo [69].…”
mentioning
confidence: 99%